Low transmission risk of African swine fever virus between wild boar infected by an attenuated isolate and susceptible domestic pigs - Kosowska, Aleksandra; Barasona, Jose A.; Barroso-Arévalo, Sandra; Blondeau Leon, Luisa; Cadenas-Fernández, Estefanía; Sánchez-Vizcaíno, Jose M. (Frontiers in Veterinary Science, 2023)
African swine fever (ASF) is a lethal infectious disease that affects domestic and wild pigs. This complex virus has already affected five continents and more than 70 countries and is considered to be the main threat to the global swine industry. The disease can potentially be transmitted directly through contact with infectious animals, or indirectly by means of contaminated feed or environments. Nevertheless, the knowledge regarding the transmission patterns of different ASF virus isolates at the wildlife-livestock interface is still limited. We have, therefore, assessed the potential transmission of an attenuated ASF virus isolate between infectious wild boar and directly exposed domestic pig. We registered 3.369 interspecific interactions between animals, which were brief and mostly initiated by wild boar. The major patterns observed during the study were head-to-head contact owing to sniffing, thus suggesting a high probability of pathogen transmission. However, only one of the five domestic pigs had a short period of viremia and became serologically positive for ASF virus antibodies. It was additionally discovered that the wild boar did not transmit the virulent virus isolate to the domestic pigs, which suggests that the presence of attenuated ASF virus isolates in affected areas may control the spreading of other more virulent isolates. These outcomes may help make decisions related to large-scale targeted management actions against ASF in field conditions.